(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article examined the specific pedagogical and psychological features of the process of preparing future teachers for innovative professional activities and focused on the great interest of teachers in scientific work in the field of theory and practice of pedagogical innovation